2017
DOI: 10.1097/sle.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Difficulty of Laparoscopic Abdominoperineal Resection for Ultra-Low Rectal Cancer

Abstract: Purpose:Our current study was conducted to identify patients’ anatomic, pathologic, and clinical factors to predict difficulty of performing laparoscopic abdominoperineal resection for ultra-low rectal cancer.Materials and Methods:Records of 117 consecutive patients with rectal cancer 2 to 5 cm from the anal verge were retrospectively reviewed. Using univariate and multivariate linear or logistic regression models, standardized operative time and blood loss, as well as postoperative morbidity were utilized as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
(34 reference statements)
1
16
0
Order By: Relevance
“…In the literature, other MRI‐based studies identified patient‐ and tumour‐related predictors of surgical difficulty . Most of them found an association between male sex and risk of conversion from laparoscopy to laparotomy , or greater tumour volume with longer operative times .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, other MRI‐based studies identified patient‐ and tumour‐related predictors of surgical difficulty . Most of them found an association between male sex and risk of conversion from laparoscopy to laparotomy , or greater tumour volume with longer operative times .…”
Section: Discussionmentioning
confidence: 99%
“…15,18,19 In the current literature, operative time and EBL are often used as surrogate markers for surgical difficulty without directly assessing surgeon-reported difficulty. [4][5][6][7][8][9] We demonstrate that EBL and opera- 20 Previous studies of laparoscopic and robotic surgery have demonstrated that pelvic measurements may impact the difficulty of pelvic surgery due to limited working space. [4][5][6][7]11,21 Using measurements including transverse pelvic diameter as well as the prostate volume:…”
Section: Discussionmentioning
confidence: 64%
“…[4][5][6][7][8][9] We demonstrate that EBL and opera- 20 Previous studies of laparoscopic and robotic surgery have demonstrated that pelvic measurements may impact the difficulty of pelvic surgery due to limited working space. [4][5][6][7]11,21 Using measurements including transverse pelvic diameter as well as the prostate volume:…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Previous studies identified several variables to predict the difficulty of rectal resections. Sex, BMI, tumour size and location, nCRT and co‐morbidity, anastomotic height, histopathological features, surgeon experience and anatomical dimensions of the pelvis were reported to be risk factors for conversion to open surgery, duration of surgery, CRM positivity and postoperative morbidity. Several MRI pelvimetric parameters have been investigated previously; however, the results were inconsistent owing to differences in sample size, the racial composition of patient populations, variables measured, and definitions of surgical difficulty used across studies.…”
Section: Discussionmentioning
confidence: 99%